2007
DOI: 10.1124/jpet.107.126110
|View full text |Cite
|
Sign up to set email alerts
|

N-Benzyladriamycin-14-valerate (AD 198): A Non-Cardiotoxic Anthracycline That Is Cardioprotective through PKC-ϵ Activation

Abstract: ) is one of several novel anthracycline protein kinase C (PKC)-activating agents developed in our laboratories that demonstrates cytotoxic superiority over doxorubicin (Adriamycin; DOX) through its circumvention of multiple mechanisms of drug resistance. This characteristic is attributed at least partly to the principal cellular action of AD 198: PKC activation through binding to the C1b (diacylglycerol binding) regulatory domain. A significant dose-limiting effect of DOX is chronic, dose-dependent, and often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…PKC-ε activation is thought to be cardioprotective through its ability to: 1) prime sarcolemma K ATP channels to reduce action potential duration and, as such, reduce Ca 2ϩ entry and Ca 2ϩ overload, 2) open mitochondrial K ATP channels to prevent Ca 2ϩ overload and volume overload of the mitochondria and reduced mitochondrial ROS production, 3) inhibit the mitochondrial permeability transition pore opening to inhibit mitochondrial swelling, cytochrome C release, and the uncoupling of oxidative phosphorylation, 4) activate protein phosphatase 1, which decreases phospho-PLB to decrease Ca 2ϩ content and Ca 2ϩ cycling, thus attenuating any rise in cytosolic [Ca 2ϩ ], and 5) activate transcription factors that increase antioxidant expression to reduce ROS overload (Bolli et al, 2007;Budas et al, 2007). In a previous study we demonstrated that AD 198 protects from ischemia-reperfusion induced cardiac dysfunction, and this benefit is not observed in PKC-ε knockout mice (Hofmann et al, 2007). In the present study we show PKC-ε inhibition blocks the ability of AD 198 to reverse Dox-induced changes in phosphorylation of AMPK and TnI (Fig.…”
Section: Protection From Doxorubicin Cardiotoxicity Using Ad 198 227mentioning
confidence: 99%
See 3 more Smart Citations
“…PKC-ε activation is thought to be cardioprotective through its ability to: 1) prime sarcolemma K ATP channels to reduce action potential duration and, as such, reduce Ca 2ϩ entry and Ca 2ϩ overload, 2) open mitochondrial K ATP channels to prevent Ca 2ϩ overload and volume overload of the mitochondria and reduced mitochondrial ROS production, 3) inhibit the mitochondrial permeability transition pore opening to inhibit mitochondrial swelling, cytochrome C release, and the uncoupling of oxidative phosphorylation, 4) activate protein phosphatase 1, which decreases phospho-PLB to decrease Ca 2ϩ content and Ca 2ϩ cycling, thus attenuating any rise in cytosolic [Ca 2ϩ ], and 5) activate transcription factors that increase antioxidant expression to reduce ROS overload (Bolli et al, 2007;Budas et al, 2007). In a previous study we demonstrated that AD 198 protects from ischemia-reperfusion induced cardiac dysfunction, and this benefit is not observed in PKC-ε knockout mice (Hofmann et al, 2007). In the present study we show PKC-ε inhibition blocks the ability of AD 198 to reverse Dox-induced changes in phosphorylation of AMPK and TnI (Fig.…”
Section: Protection From Doxorubicin Cardiotoxicity Using Ad 198 227mentioning
confidence: 99%
“…The chemical modifications of Dox that produce AD 198 creates a domain within AD 198 that has a structural similarity to diacyglycerol, an endogenous ligand for protein kinase C (Roaten et al, 2001). We have shown previously AD 198 binds to PKC at its diacyglycerol binding site and this activates PKC-ε in cardiomyocytes (Hofmann et al, 2007). PKC-ε activation is thought to be cardioprotective through its ability to: 1) prime sarcolemma K ATP channels to reduce action potential duration and, as such, reduce Ca 2ϩ entry and Ca 2ϩ overload, 2) open mitochondrial K ATP channels to prevent Ca 2ϩ overload and volume overload of the mitochondria and reduced mitochondrial ROS production, 3) inhibit the mitochondrial permeability transition pore opening to inhibit mitochondrial swelling, cytochrome C release, and the uncoupling of oxidative phosphorylation, 4) activate protein phosphatase 1, which decreases phospho-PLB to decrease Ca 2ϩ content and Ca 2ϩ cycling, thus attenuating any rise in cytosolic [Ca 2ϩ ], and 5) activate transcription factors that increase antioxidant expression to reduce ROS overload (Bolli et al, 2007;Budas et al, 2007).…”
Section: Protection From Doxorubicin Cardiotoxicity Using Ad 198 227mentioning
confidence: 99%
See 2 more Smart Citations
“…An-other anthracycline with protein kinase C-activating properties (AD 198) has also shown significant anti-tumor activity. However, unlike DOX, little ventricular damage was observed in mice administered the agent [175].…”
Section: V) Synthesis Of Non-cardiotoxic Anthracyclinesmentioning
confidence: 98%